Synthesis of Curcumin Derivative Assisted by Microwave Irradiation - Sabtanti Harimurti; Winny Setyonugroho; Ardi Pramono; Rizky Hidayaturahmah (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2019)
Synthesis of curcumin derivate is commonly conducted using conventional heating like heating mantel. The synthesis was usually done in the very long time. An experiment on finding an efficient synthesis method may be necessary to conduct, such as using microwave to replace the energy source. The synthesis of curcumin derivate 1,5-bis(4’-hydroxy-3’-metoxyphenyl)-1,4-pentadiene-3-one or gamavuton-0 assisted by microwave irradiation has been carried out. This synthesis was done on propose of cancer drug discovery to answer the search of new cancer drug on the increase of cancer incidence recently. The synthesis was done under microwave irradiation using vanillin and acetone as the starting material, and hydrochloric acid as the catalyst. Based on the experimental data, the microwave irradiation significantly reduces the reaction time. By using microwave irradiation, the synthesis can be done in a short time.